Multiomics Analysis Reveals Molecular Abnormalities in Granulosa Cells of Women With Polycystic Ovary Syndrome - Zhao, Rusong; Jiang, Yonghui; Zhao, Shigang; Zhao, Han (Frontiers in Genetics, 2021)
Polycystic ovary syndrome (PCOS) is the most common complex endocrine and metabolic disease in women of reproductive age. It is characterized by anovulatory infertility, hormone disorders, and polycystic ovarian morphology. Regarding the importance of granulosa cells (GCs) in the pathogenesis of PCOS, few studies have investigated its etiology at a single “omics” layer, such as with an mRNA expression array or methylation profiling assay, but this can only provide limited insights into the biological mechanisms. Here, the genome-wide DNA methylation together with lncRNA-miRNA-mRNA profiles were simultaneously detected in GCs of PCOS cases and controls. A total of 3579 lncRNAs, 39 miRNAs, 669 mRNAs, and 890 differentially methylated regions (DMRs)-associated genes were differentially expressed between PCOS cases and controls. Pathway analysis indicated that these differentially expressed genes were commonly associated with steroid biosynthesis and metabolism related signaling, such as glycolysis/gluconeogenesis. In additions, we constructed the ceRNA networks and identified some traditional loops, like lncRNAs-miR-628-5p-CYP11A1/HSD17B7. And we also identified many new ceRNA loops such as lncRNAs-miR-483-5p-GOT2. Interestingly, most ceRNA loops were also closely related to steroid biosynthesis and metabolic pathways. These findings may remind us to systematically consider the role of reproductive and metabolic related genes in the pathogenesis of PCOS.